Terms-of-Trade Shocks are Not all Alike. (IMF Working Papers; Working Paper ;, 2020)
When analyzing terms-of-trade shocks, it is implicitly assumed that the economy responds symmetrically to changes in export and import prices. Using a sample of developing countries our paper shows that this is not the case. We construct export and import price indices using commodity and manufacturing price data matched with trade shares and separately identify export price, import price, and global economic activity shocks using sign and narrative restrictions. Taken together, export and import price shocks account for around 40 percent of output fluctuations but export price shocks are, on average, twice as important as import price shocks for domestic business cycles.